Agentic Group Guidance Services to Improve the Meaning of Life of Minangkabau Ethnic Adolescents - Afdha Lianti; Herman Nirwana; Yeni Karneli; Rezki Hariko; Siska Pratiwi (STAI Hubbulwathan Duri, 2026)
Meaning of life is a fundamental psychological need that influences adolescents’ well-being, motivation, and identity development. In the Minangkabau cultural context, philosophical values such as “hidup bajaso, mati bapusako” emphasize purposeful living and meaningful contribution. However, many adolescents demonstrate moderate to low levels of life meaning, indicating the need for culturally responsive counseling interventions. This study aimed to examine the effectiveness of agentic group guidance in improving the meaning of life among Minangkabau ethnic adolescents. This study employed a quantitative quasi-experimental design using a non-equivalent control group pretest–posttest model. Twenty Minangkabau students with moderate to low levels of meaning of life were selected through purposive sampling and assigned to an experimental group (n = 10) and a control group (n = 10). The experimental group received six sessions of agentic group guidance, while the control group received conventional guidance services. Data were collected using the Meaning of Life Questionnaire (α = 0.87) and analyzed using Wilcoxon Signed Rank Test and Mann–Whitney U Test. The findings revealed a significant increase in meaning of life scores in the experimental group after the intervention. Furthermore, posttest comparisons indicated that the improvement in the experimental group was significantly higher than that of the control group. These results suggest that agentic group guidance is an effective and culturally relevant intervention for enhancing adolescents’ meaning of life. Integrating agency principles with local cultural values can strengthen students’ self-direction, goal setting, and psychological development in school settings.